Guest editorial - NAAMAN, Nada (International Arab Journal of Dentistry (IAJD), 2010)
The Society of Arab Dental Faculties (SARDF) affiliated to the Association of Arab Universities has decided to launch the International Arab Journal of Dentistry in order to bring together the scientific publications of faculty members...